LEVEL OF PREFERENCE KATTE TONG COOKIES WITH ADDITION PANGASIUS CATFISH MEAT FLOUR - Irpan Irpan; Junianto Junianto; Roffi Grandiosa Herman; Iis Rostini (Universitas Mataram, 2024)
Pangasius catfish has the potential to be processed into flour because it has a high protein content in its meat. Food processing with the addition of pangasius catfish meat flour has not been widely done, so it is necessary to know the right concentration so that it can be accepted by consumers. This study aims to determine the level of addition of pangasius catfish meat flour concentration that is most preferred by consumers in katte tong cookies products. The method used is an experimental method with four treatments, namely 0%, 7.5%, 10%, and 12.5%. The results showed that the addition of pangasius catfish meat flour influenced the organoleptic test. The addition of 10% pangasius catfish meat flour is the best treatment for katte tong cookies with an appearance value of 7.4, aroma 7.0, texture 7.5, and taste 7.5.